Pembinaan Akhlak Remaja Melalui Komunikasi Interpesonal dalam Keluarga (Analisis Sugesti dalam Hypnoparenting) - Faridah Faridah; Muhammad Yusuf; Asriadi Asriadi (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2021)
This study discusses the Development of Adolescent Morals through Interpersonal Communication in the Family by analyzing the impact of suggestion in hypnoparenting. This research is a form of qualitative research by conducting field studies (field research) which seeks to reveal about social phenomena and certain social aspects in the family and community being studied. The rise of juvenile delinquency both in big cities and in rural areas is a matter of great concern and requires problem solving to cope with the increasing prevalence of juvenile delinquency. The family as the main foundation for the formation of adolescent behavior needs to make improvements in all aspects, especially in the psycho-social and religious aspects of adolescents. Interpersonal communication in the family can create intimacy and familiarity with the perpetrators, making the relationship between family members, especially between parents and their children, like a pair of friends or best friends. Interpersonal communication activities carried out by parents to children contain suggestions that play an important role in children's cognitive, affective and psychomotor changes. Positive suggestions given by parents in the communication activities carried out can have a positive impact and negative suggestions can have a negative impact so that the role of interpersonal communication with the hypnosis method through positive suggestions can be a reference in the education of children in the family.